Evaluation of the Anti-Inflammatory and Antinociceptive Effects of the Essential Oil from Leaves of Xylopia laevigata in Experimental Models - João Carlos C. Queiroz; Ângelo R. Antoniolli; Lucindo J. Quintans-Júnior; Renan G. Brito; Rosana S. S. Barreto; Emmanoel V. Costa; Thanany B. da Silva; Ana Paula Nascimento Prata; Waldecy de Lucca; Jackson R. G. S. Almeida; Julianeli T. Lima; Jullyana S. S. Quintans (The Scientific World Journal)
Xylopia laevigata (Annonaceae) is a medicinal plant used in folk medicine to treat pain and inflammation. Thus, we investigated the possible antioxidant, antinociceptive, and anti-inflammatory effects of X. laevigata leaf essential oil (EOX) in animal models. Our EOX sample showed the presence of γ-muurolene (17.78%), δ-cadinene (12.23%), bicyclogermacrene (7.77%), and α-copaene (7.17%) as main compounds. EOX presented a strong antioxidant potential according to the DPPH, TBARS, and nitrite production tests. Additionally, pretreatment with EOX, in mice, also significantly produced (P<0.05 or P<0.001) antinociceptive effect by reduction of nociceptive behavior (in formalin and writhing tests). The EOX showed c-Fos label in the olfactory bulb, piriform cortex, and periaqueductal gray. Acute administration of EOX exhibited a significant (P<0.01 or P<0.001) anti-inflammatory profile in the carrageenan-induced peritonitis and by the carrageenan-induced hindpaw edema tests in mice. Our results provide evidence for the use of X. laevigata by traditional medicine practitioners in the management of pain and inflammatory disorders.